Factors That Influence Muslim Consumers Preference Towards Islamic Banking Products Or Facilities - Theory Of Reasoned Action - Jahya, Noresma (2004)
The purpose of this study is to identify the determinants of Muslim consumers’ intention whether to engage in Islamic banking facilities or not to engage. Ajzen and Fishbein’s (1980) Theory of Reasoned Action was used as a basis for this study. The theory posits that the immediate determinant of behavior is intention. Intention is determined by the weighted attitude toward the behavior and the weighted subjective norm. The variables under studied in this research were actual behavior, intention, attitude toward the behavior, subjective norm, and the external variables i.e. knowledge and religiosity. Combination of beliefs, evaluations, and motivation to comply determined attitude and subjective norm towards behavior.